Social and Emotional Characteristics and Early Childhood Mathematical and Literacy Giftedness: Observations From Parents and Childcare Providers Using the ECLS-B. (December 2015) - Wilson, Hope E.
Research has demonstrated mixed results regarding differences in social and emotional characteristics between gifted and typical populations. The purpose of this secondary analysis of data from the Early Childhood Longitudinal Study: Birth Cohort (ECLS-B) is to investigate the affective characteristics of early mathematics and literacy ability among preschool children using a logistic regression analysis. Specifically, parents and childcare providers were asked a series of questions relating to socially maladaptive behaviors, concentration, empathy, worry, and friendship of a nationally representative sample of children born in 2002. The results of the study demonstrate that childcare providers and parents of preschool children ( M age = 53 months) have different patterns of observations of social and emotional characteristics of children, and that concentration and socially maladaptive behaviors were significant predictors of early giftedness in literacy. There were no social or emotional predictors of early giftedness in mathematics found in this study.